Atmospheric‐Pressure Synthesis of 2D Nitrogen‐Rich Tungsten Nitride. Issue 51 (24th October 2018) - Yu, Huimin; Yang, Xin; Xiao, Xu; Chen, Ming; Zhang, Qinghua; Huang, Liang; Wu, Jiabing; Li, Tianqi; Chen, Shuangming; Song, Li; Gu, Lin; Xia, Bao Yu; et al.
Abstract: 2D transition metal nitrides, especially nitrogen‐rich tungsten nitrides (W x N y, y > x ), such as W3 N4 and W2 N3, have a great potential for the hydrogen evolution reaction (HER) since the catalytic activity is largely enhanced by the abundant WN bonding. However, the rational synthesis of 2D nitrogen‐rich tungsten nitrides is challenging due to the large formation energy of WN bonding. Herein, ultrathin 2D hexagonal‐W2 N3 ( h ‐W2 N3 ) flakes are synthesized at atmospheric pressure via a salt‐templated method. The formation energy of h ‐W2 N3 can be dramatically decreased owing to the strong interaction and domain matching epitaxy between KCl and h ‐W2 N3 . 2D h ‐W2 N3 demonstrates an excellent catalytic activity for cathodic HER with an onset potential of −30.8 mV as well as an overpotential of −98.2 mV for 10 mA cm −2 . Abstract : Ultrathin 2D hexagonal‐W2 N3 ( h ‐W2 N3 ) flakes are synthesized at atmospheric pressure via a salt‐templated method. The formation energy of h ‐W2 N3 can be dramatically decreased owing to the strong interaction and domain matching epitaxy between KCl and h ‐W2 N3 . 2D h ‐W2 N3 demonstrates an excellent catalytic activity for the cathodic hydrogen evolution reaction.